Heat Shock Protein 90 of Bonamia ostreae: Characterization and Possible Correlation with Infection of the Flat Oyster, Ostrea edulis. (12th March 2013) - Prado‐Alvarez, Maria; Chollet, Bruno; Couraleau, Yann; Morga, Benjamin; Arzul, Isabelle
Abstract: In this study, we described the cytosolic HSP90 of Bonamia ostreae, an intracellular parasite of Ostrea edulis hemocytes. The complete open reading frame was assembled by Rapid Amplification cDNA Ends reactions on cDNA of B. ostreae ‐infected hemocytes. HSP90 amplification was corroborated in infected oysters and B. ostreae purified cells. The functionality of the HSP90, studied by inhibitory assays with radicicol, suggests that this protein may play a role in hemocyte invasion. Our results inform the molecular basis that governs B. ostreae–O. edulis interactions.